Binny for short - McKay, Hilary; Player, Micah (New York : Margaret K. McElderry Books, 2013)
Eleven-year-old Binny struggles to cope with her father's death and the loss of her beloved dog while she adjusts to a new home that might be haunted by her horrible Aunt Violet.
Ages 8-12.
Keywords: Family life -- Fiction; Loss (Psychology) -- Fiction; Moving, Household -- Fiction; Families -- Juvenile fiction; Loss (Psychology) -- Juvenile fiction; Moving, Household -- Juvenile fiction; Families; Loss (Psychology); Moving, Household; Fiction; Juvenile works